Politics by other means? STS and research in education. Issue 1 (2nd January 2019) - Gorur, Radhika; Hamilton, Mary; Lundahl, Christian; Sjödin, Elin Sundström
ABSTRACT: Science and Technology Studies (STS) has been surprisingly slow to become widely known and deployed in the field of education. Yet STS has a rich array of concepts and analytical methods to offer to studies of: knowledge practices and epistemic cultures; the interrelationship between states and knowledge; regulatory practices, governance and institutions; and classrooms, pedagogy, teaching and learning. Most importantly, it provides a fresh perspective on how power operates in ordering societies, disciplining actors and promoting ideas and practices. In this paper, we provide an introduction to STS and elaborate what it offers education scholars. Using examples from the emerging body of STS work in the field of education, and in particular from the papers in this special issue, we argue that STS is not only useful, but an exciting and generative form of critique – one that is especially suited to investigating contemporary issues in education policies and practices.